2020
DOI: 10.1073/pnas.2005857117
|View full text |Cite
|
Sign up to set email alerts
|

Short Vi-polysaccharide abrogates T-independent immune response and hyporesponsiveness elicited by long Vi-CRM197conjugate vaccine

Abstract: Polysaccharide-protein conjugates have been developed to overcome the T-independent response, hyporesponsiveness to repeated vaccination, and poor immunogenicity in infants of polysaccharides. To address the impact of polysaccharide length, typhoid conjugates made with short- and long-chain fractions of Vi polysaccharide with average sizes of 9.5, 22.8, 42.7, 82.0, and 165 kDa were compared. Long-chain-conjugated Vi (165 kDa) induced a response in both wild-type and T cell-deficient mice, suggesting that it ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
(59 reference statements)
0
31
0
Order By: Relevance
“…Moreover, we have recently verified the ability of S. sonnei GMMA to boost the immune response in healthy European adults primed 2–3 years earlier [ 29 ]. Therefore, while polysaccharide length can dramatically impact the ability of glycoconjugate vaccines to induce T-independent responses [ 18 ], it might have a more limited role in the complex immunological response to GMMA [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have recently verified the ability of S. sonnei GMMA to boost the immune response in healthy European adults primed 2–3 years earlier [ 29 ]. Therefore, while polysaccharide length can dramatically impact the ability of glycoconjugate vaccines to induce T-independent responses [ 18 ], it might have a more limited role in the complex immunological response to GMMA [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, when comparing typhoid conjugates made with short- or long-chain Vi polysaccharide, long–chain-conjugated Vi (165 kDa) induced a response in both wild-type and T-cell-deficient mice, while short-chain Vi (9.5 to 42.7 kDa) conjugates induced a response in wild-type mice but not in T-cell-deficient mice. This suggested that the response elicited by longer Vi chains was partially T-independent, consequently resulting in hyporesponsiveness [ 18 ]. Selection of optimal length in glycoconjugates can avoid detrimental effects on memory and subsequent boosting.…”
Section: Introductionmentioning
confidence: 99%
“…For a full-sized antigen, the response was similar irrespective of protein conjugate, but in formulation with fragmented Vi, after second immunisation a booster response was only observed with TT but not with CRM 197 and DT that may be linked to the larger size of TT as well as its T-cell epitopes (Arcuri et al 2017 ; Wessels et al 1998 ; Lockyer et al 2020 ). With a CRM 197 conjugate, Vi PS of less than 50 kDa gave a booster dose, while full-length Vi PS led to hypo-responsiveness (Micoli et al 2020a , b ). Although Vi-CRM 197 and Vi- r EPA behaved differently when tested in infants, the source and size of Vi PS were different, and these factors should also be considered (Thiem et al 2011 ; Bhutta et al 2014 ; Micoli et al 2020a , b ).…”
Section: Part IImentioning
confidence: 99%
“…With a CRM 197 conjugate, Vi PS of less than 50 kDa gave a booster dose, while full-length Vi PS led to hypo-responsiveness (Micoli et al 2020a , b ). Although Vi-CRM 197 and Vi- r EPA behaved differently when tested in infants, the source and size of Vi PS were different, and these factors should also be considered (Thiem et al 2011 ; Bhutta et al 2014 ; Micoli et al 2020a , b ). Another study has also confirmed that immune response to Vi-DT in mice was stronger with an increasing amount of cross-linking and the subsequent size of the conjugate (An et al 2011 ).…”
Section: Part IImentioning
confidence: 99%
See 1 more Smart Citation